Bark coverage shifts assembly processes of microbial decomposer communities in dead wood. Issue 1912 (9th October 2019) - Hagge, Jonas; Bässler, Claus; Gruppe, Axel; Hoppe, Björn; Kellner, Harald; Krah, Franz-Sebastian; Müller, Jörg; Seibold, Sebastian; Stengel, Elisa; Thorn, Simon
Abstract : Bark protects living trees against environmental influences but may promote wood decomposition by fungi and bacteria after tree death. However, the mechanisms by which bark determines the assembly process and biodiversity of decomposers remain unknown. Therefore, we partially or completely removed bark from experimentally felled trees and tested with null modelling whether assembly processes were determined by bark coverage and if biodiversity of molecularly sampled fungi and bacteria generally benefited from increasing bark cover. The community composition of fungi, wood-decaying fungi (subset of all fungi) and bacteria clearly separated between completely debarked, partly debarked and control trees. Bacterial species richness was higher on control trees than on either partly or completely debarked trees, whereas the species richness of all fungi did not differ. However, the species richness of wood-decaying fungi was higher on partially and completely debarked trees than on control trees. Deterministic assembly processes were most important in completely debarked trees, a pattern consistent for fungi and bacteria. Our findings suggest that human disturbances in forests shift the dominant assembly mechanism from stochastic to deterministic processes and thus alter the diversity of wood-inhabiting microorganisms.